Duodenal atresia with apple peel jejunoileal syndrome - Taís Wong; Fábio Volpe; Md F.G. Tazima; W.C. Canesin; Lourenço Sbragia (Elsevier, 2021)
Embryologically, duodenal atresia results from inadequate recanalization and proliferation of the solid cord in the 8-10th week of gestation, while apple-peel atresia is a consequence of a vascular accident. The presence of both malformations is rather rare. We report a case with both associations; to our knowledge, this is the twelfth such case reported in the English literature.